Leading in the midst of it all : surviving and thriving through Covid-19 and racial reckonings - Alexander, Sheree N.; Griffen, Aaron J.; Williams, C. Dedra; Griffen, Karen (Research, advocacy, collaboration, and empowerment mentoring series., 2025)
Leading in the Midst of it All: Surviving and Thriving Through COVID-19 and Racial Reckonings centers educators of color--both P-12 and Higher Education--during national pandemics and political, civil, and racial unrest. This volume offers firsthand experiences of recognizing and addressing inequities and their impact on communities. It shares how educators of color led amidst competing pandemics while serving their schools, communities, and families. The authors provide practical insights for P-12 educators and Higher Educators on addressing disparities in remote instruction, hiring, retention, and development, while creating inclusive and engaging virtual and hybrid schooling experiences. Leading in the Midst of it All highlights the necessity for human resource personnel, school leadership programs, superintendents, college presidents, provosts, and boards to value the lived experiences of educators of color and provide intentional support. The book is divided into four sections. Section I focuses on the experiences of teachers of color, detailing the impacts of COVID-19 on marginalized communities. Section II centers on school leadership, particularly leaders of color, as they navigate their roles amidst social inequities. Section III engages the narratives of central office personnel of color, emphasizing the value of revolutionary voices to disrupt inequitable ideologies. Section IV provides details on policy, practice, and partnership transformation methods that empower sustainability for practitioners and researchers. The chapters in this book capture the daily challenges of leading amidst pandemics, fear, unrest, and uncertainty.